2017
DOI: 10.1111/1750-3841.13653
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Thermal, Physical, Mechanical, and Barrier Properties of Chitosan Films with the Addition of Xanthan Gum

Abstract: Films based on chitosan and xanthan gum were prepared using casting technique aiming to investigate the potential of these polymers as packaging materials. Six formulations of films were studied varying the proportion of chitosan and xanthan gum: 100:0 (chitosan:xanthan gum, w/w, C100XG0 film); 90:10 (chitosan:xanthan gum, w/w, C90XG10 film); 80:20 (chitosan:xanthan gum, w/w, C80XG20 film); 70:30 (chitosan:xanthan gum, w/w, C70XG30 film); 60:40 (chitosan:xanthan gum, w/w, C60XG40 film); and 50:50 (chitosan:xan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 35 publications
(45 reference statements)
12
36
2
Order By: Relevance
“…It was known that DSC was a useful and rapid method to measure the interrelated thermodynamic profiles, and it was usually used to determine the temperature and enthalpy during endothermic or exothermic processes for an application in polymer materials [8]. The thermograms of DSC analysis and the related peak temperatures were given and illustrated in Figure 3.…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was known that DSC was a useful and rapid method to measure the interrelated thermodynamic profiles, and it was usually used to determine the temperature and enthalpy during endothermic or exothermic processes for an application in polymer materials [8]. The thermograms of DSC analysis and the related peak temperatures were given and illustrated in Figure 3.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Indeed, more and more attention has been paid to develop edible films in order to improve food safety and shelf-life [8][9][10]. Edible films need to possess the appropriate mechanical properties and barrier properties from initial product packing to final consumer usage [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of biodegradable materials, such as polysaccharides and protein farinaceous substances, have been studied. In addition, more researchers are increasingly interested in the development of antibacterial biodegradable materials Lima et al, GE-based films are hygroscopic, flexible, and exhibit relatively poor mechanical properties (Alves et al, 2018). Therefore, blends of CS and GE were often used to prepare biocomposite packaging materials to achieve desirable moisture resistance and mechanical properties (Ferreira et al, 2016;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The use of xanthan gum a non-gelling nature, as an alternative crosslinking agent in gelatin/carboxymethylcellulose film blend have formed a blend of composite film and improved several physical and mechanical properties of gelatin/carboxymethylcellulose film blend alone. Results Lima et al [31] demonstrated that films containing higher content of xanthan gum show the highest tensile strength and the lowest elongation. Xanthan gum addition did not affect the water vapor permeability, solubility, and moisture of films.…”
Section: Physical Properties Of Obtained Lyophilized Protein Structuresmentioning
confidence: 99%